Pengaruh Senam Yoga dan Terapi Musik Klasik Mozart Terhadap Tingkat Kecemasan Menghadapi Persiapan Persalinan Pada Ibu Hamil Trimester III di Puskesmas Tempel 2 - Lysa Novadianti; Widya Mariyana; Mudy Oktiningrum (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
The trimester III pregnant women at Public Health Care Tempel 2 were anxious while preparing for their delivery, such as the anxiety of giving birth abnormally, the fear of incapability to endure the labor pain, the situation of the pregnant women after giving birth, the unwanted delivery, and the situation of not meeting the babies after the delivery. This research determined the influence of Yoga calisthenics and classic Mozart therapy on the anxiety level of trimester III pregnant women at Public Health Care Tempel 2. This quantitative research applied a pre- experimental model with a one-group-pretest-posttest design. The population consisted of 50 trimester III pregnant women at Public Health Care Tempel 2. The researcher took 33 pregnant women as the samples with a purposive sampling technique. The researcher analyzed the data with Shapiro-Wilk. The result showed a p-value of 0.000, indicating abnormal data distribution. The result of the Wilcoxon test obtained a p-value of 0.000. The result denies Ho and accepts Ha, indicating the influence of Yoga calisthenics and classic Mozart music therapy on the anxiety level while preparing for the delivery of trimester III pregnant women. From the Wilcoxon test, the obtained Z-count is 4.347. From the Wilcoxon test, the researcher found the Z-count was 4.347, indicating Yoga calisthenics and classic Mozart therapy could relieve the anxiety of the respondents by 4.347 while preparing for their delivery. The implementations of Yoga calisthenics and classic Mozat music therapy influence the endocrine hormone to relieve the anxiety while preparing the delivery and make the trimester III pregnant women relax.